Black Out-group Marriages and Hate Crime Rates: A Cross-sectional Analysis of U.S. Metropolitan Areas. (February 2020) - Piatkowska, Sylwia J.; Messner, Steven F.; Hövermann, Andreas
Objectives: This study introduces an indicator of racial out-group marriage to the research on hate crime. Drawing upon a variant of group threat theory, we hypothesize that Black out-group marriage with Whites will be positively related to anti-Black hate crime rates insofar as such marriages are perceived as transgressions of cultural boundaries. Informed by Allport's contact theory, we hypothesize that Black out-group marriage with Whites will be negatively related to anti-Black hate crime rates insofar as such marriages indicate intercultural accommodation. Methods: Using data for a sample of U.S. Metropolitan Statistical Areas circa 2010, we assess our hypotheses with two operationalizations of levels of hate crime—incidence rates and victimization rates. Results: Our results reveal that levels of Black out-group marriages with Whites are positively related to the Black hate crime victimization rate but not related to the incidence rate. Conclusions: Our analyses suggest that any salutary effect of intercultural accommodation associated with interracial marriage is overwhelmed by the influence of the perceived cultural threat and intensification of animus for the "at-risk" population for perpetrating anti-Black hate crimes.